دور الشريعة الإسلامية في ترسيخ مبادئ الحوكمة: مدى إلزامية الوعد في المصارف الإسلامية نموذجاً (The Role of Shariah in Consolidating the Principles of Governance: The Study of the Extent of Mandatory Promise in Islam) - ميسون قوادري; عارف علي عارف; حسن بن إبراهيم الهنداوي, (Journal of Islam in Asia (E-ISSN 2289-8077), 2019)
يشهد العصر الراهن نموا معتبرا في حجم المؤسسات المصرفية الإسلامية؛ ما ترتب عنه زيادة الحاجة للاهتمام بأساليب التنظيم الإدارية والشرعية في هذه المؤسسات؛ لتحقيق أهدافها التي أنشأت من أجلها وتلبية رغبات أفراد المجتمع المسلمين وغير المسلمين ممن يرغبون في التعامل معها؛ لذا يأتي هذا البحث لبيان ماهية الحوكمة الشرعية في المصارف الإسلامية وعلاقتها بنظام هذه المؤسسات والتركيز على مبدأ الوفاء بالوعد وبيان مدى إلزاميته وعلاقته بمبادئ الحوكمة وذلك لإبراز السبق العلمي والدور الأساسي للشريعة الإسلامية في ترسيخ قواعد الحوكمة في جانب من جوانبها وأنها كفيلة باستقرار المعاملات بصفة عامة والمعاملات المالية بصفة خاصة بما تحويه من مبادئ سامية، وسينتهج البحث المنهج التحليلي لتحليل أقوال الفقهاء حول مسألة الوعد الملزم، والمنهج الوصفي لبيان مبادئ الحوكمة، وعلاقتها بمبادئ الشريعة الإسلامية السمحاء. الكلمات المفتاحيّة: الوعد، حكم الوعد، الحوكمة، مقاصد الشريعة الإسلامية، المصارف الإسلامية. Abstract The present epoch is witnessing a significant growth in the Islamic banking institutions, which has led to an increase of need of methods of administrative and legal in these institutions in order to achieve the objectives for which they were established and to meet the desire of Muslim and non-Muslim community members who wish to deal with them. Therefore, this study aims to discuss the essence of Islamic governance in Islamic banks and their relationship to the system of these institutions as well as to focus on the principle of fulfilling the promise and to show the extent of its mandatory and its relationship to the principles of governance. Hence, the study highlights the basic role of Islamic law in consolidating the principles of governance. These kind of principles securing the stability of transactions generally and financial transactions particularly, which containing exalted principles. This study used the analytical approach to analyze the statements of jurists on the issues of binding promise, as well as descriptive approach to explain the principles of governance and its relation to the principles of Islamic law. Keywords: Promise, Governance, The goal of Islamic laws, Islamic banks.